The global flood protection savings provided by coral reefs - Michael W. Beck (Nature Portfolio, 2018)
Coral reefs provide significant coastal protection from storms but they have experienced significant losses. Here the authors show that the annual damages from flooding would double globally without reefs and they quantify where reefs provide the most protection to people and property.